Duchenne Smiles as Honest Signals of Chronic Positive Mood. (May 2021) - Sheldon, Kennon M.; Corcoran, Mike; Sheldon, Melanie
Chronic positive mood (CPM) has been shown to confer a wide variety of social, functional, and health benefits. Some researchers have argued that humans evolved to feel CPM, which explains why most people report better than neutral mood (the "positivity offset bias") and why particularly happy people have particularly good outcomes. Here, we argue that the Duchenne smile evolved as an honest signal of high levels of CPM, alerting others to the psychological fitness of the smiler. Duchenne smiles are honest because they express felt positive emotion, making it difficult for unhappy people to produce them. Duchenne smiles enable happy people to signal and cooperate with one another, boosting their advantages. In our literature review, we found (a) that not all Duchenne smiles are "honest, " although producing them in the absence of positive emotion is difficult and often detectable, and (b) that the ability to produce and recognize Duchenne smiles may vary somewhat by a person's cultural origin. In the final section of the article, we consider behavioral influences on CPM, reviewing research showing that engaging in eudaimonic activity reliably produces CPM, as posited by the eudaimonic-activity model. This research suggests that frequent Duchenne smiling may ultimately signal eudaimonic personality as well as CPM.